OXIDIZED-LOW DENSITY LIPOPROTEIN DAN DERAJAT STENOSIS PENYAKIT JANTUNG KORONER (Oxidized-Low Density Lipoprotein and Stenosis Level in Coronary Artery Disease) - Sutamti Sutamti; Purwanto AP; MI. Tjahjati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Coronary artery disease is caused by atherosclerosis of the coronary arteries. Ox-LDL plays a role in atherosclerosis causing coronaryartery stenosis. There are differences in the research results on the relationship of ox-LDL levels and stenosis level of coronary arteryin patients with CAD. The aim of this study was to know the correlation between ox-LDL and stenosis level of coronary artery inCoronary Artery Disease (CAD). An observational study with cross sectional analytic approach was conducted on 37 patients with CADwho underwent coronary angiography in the Dr. Kariadi General Hospital and Telogorejo Hospital of Semarang, taken consecutivelyduring Febuary up to April 2014. The Ox-LDL levels were determined by sandwich ELISA and the stenosis levels were determined bycoronary angiography. The data were analyzed by non-parametric Spearman correlation test. Median of ox-LDL level in CAD patientswas 1666.8(846.15; 3324) pg/mL. The median of stenosis level was 80 (30;90)%. There was a significant correlation of ox-LDL leveland stenosis level (r=0.358; p=0.03) in CAD patients. Based on this study there was a weak positive correlation between ox-LDL leveland stenosis level in CAD patients.